Epidermal growth factor receptor and AKT1 gene copy numbers by multi‐gene fluorescence in situ hybridization impact on prognosis in breast cancer. Issue 5 (16th March 2015) - Li, Jiao; Su, Wei; Zhang, Sheng; Hu, Yunhui; Liu, Jingjing; Zhang, Xiaobei; Bai, Jingchao; Yuan, Weiping; Hu, Linping; Cheng, Tao; Zetterberg, Anders; Lei, Zhenmin; et al.
<x xml:space="preserve">Abstract</x> The epidermal growth factor receptor (EGFR)/PI3K/AKT signaling pathway aberrations play significant roles in breast cancer occurrence and development. However, the status of EGFR and AKT1 gene copy numbers remains unclear. In this study, we showed that the rates of EGFR and AKT1 gene copy number alterations were associated with the prognosis of breast cancer. Among 205 patients, high EGFR and AKT1 gene copy numbers were observed in 34.6% and 27.8% of cases by multi‐gene fluorescence in situ hybridization, respectively. Co‐heightened EGFR/AKT1 gene copy numbers were identified in 11.7% cases. No changes were found in 49.3% of patients. Although changes in EGFR and AKT1 gene copy numbers had no correlation with patients' age, tumor stage, histological grade and the expression status of other molecular makers, high EGFR (P = 0.0002) but not AKT1 (P = 0.1177) gene copy numbers correlated with poor 5‐year overall survival. The patients with co‐heightened EGFR/AKT1 gene copy numbers displayed a poorer prognosis than those with tumors with only high EGFR gene copy numbers (P = 0.0383). Both Univariate (U) and COX multivariate (C) analyses revealed that high EGFR and AKT1 gene copy numbers (P = 0.000 [U], P = 0.0001 [C]), similar to histological grade (P = 0.001 [U], P = 0.012 [C]) and lymph node metastasis (P = 0.046 [U], P = 0.158 [C]), were independent prognostic indicators of 5‐year overall survival. These results indicate that high EGFR and AKT1 gene copy numbers were relatively frequent in breast cancer. Co‐heightened EGFR/AKT1 gene copy numbers had a worse outcome than those with only high EGFR gene copy numbers, suggesting that evaluation of these two genes together may be useful for selecting patients for anti‐EGFR‐targeted therapy or anti‐EGFR/AKT1‐targeted therapy and for predicting outcomes.